(untitled) (Journal of Laboratory Animal Science, 2022)
Osteoarthritis is one of the common joint degenerative disorders for which only symptomatic treatment is available. In the present study we have investigated anti arthritic activity of the Methanolic extracts of the pods of Acacia nilotica in papain induced osteoarthritis model which mimics the human arthritis. Osteoarthritis was induced in rats by intra articular injection of 0.8mg of papain and 0.03M of cysteine on day 0, 4 and 7. Methanol extract of A.nilotica pods was administered to the animals in the doses of 100, 200, and 400 mg/kg for 15 days after the injection of papain and cysteine. Celecoxib (30 mg/kg) was used as the reference standard drug. The joint activity was assessed by wire hang test and measurement of the knee joint diameter. At the end of 15 days blood samples were collected for the analysis of TNFα, and IL-10 gene expression by Real Time PCR. The animals were sacrificed and the knee of the each animal was collected for the histological studies of the joint.Injection of papain with cysteine produced a significant increase in joint diameter and reduction in joint strength as depicted by decrease in wire hanging time. The Methanolic extract of A.nilotica pods produced time and dose dependent decrease in swelling of the knee joint along with significant increase in joint strength. There was a significant elevation of TNF-α as well as IL-10 gene expression in the rats treated with 400 mg/kg of test extract. Celecoxib or lower doses of A. nilotica produced slight increase in these levels. Histopathological studies revealed that the reversal of damages in the cartilage induced by papain and cysteine after administration of the extract.